Safety of Monoclonal Antibodies in Children Affected by SARS-CoV-2 Infection - Lorenza Romani; Francesca Ippolita Calò Carducci; Sara Chiurchiù; Laura Cursi; Maia De Luca; Martina Di Giuseppe; Andrzej Krzysztofiak; Laura Lancella; Paolo Palma; Leonardo Vallesi; Tiziana Corsetti; Andrea Campana; et al. (MDPI AG, 2022)
Monoclonal antibody therapies for COVID-19 have been frequently used in adults, whereas there are little data regarding the safety or efficacy of monoclonal antibody treatments in pediatric patients affected by COVID-19. We report our experience in the administration of mAb as a treatment for SARS-CoV-2 infection in children aged from 24 days to 18 years old.